THE DISCOURS OF CORPOREALITY IN THE IMAGE OF A UKRAINIAN WOMAN (ON THE MATERIAL OF V. LYS’S NOVEL «SOLO FOR SOLOMIA» - Ушневич, С. Е. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The paper is devoted to the research of the discourse of physicality in the perception if the world by a traditional-patriarchal herane comprehension of behavioural patterns of a demonic woman through the prism of mythological proto-foundations; analysis of the concept of the human being unfolded through the images of Mother, Daughter, Granddaughter.